A Thorny Path $1 (BVolume 12s - Ebers, Georg, 1837-1898; Bell, Clara, 1834-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Thorny Path $1 (BVolume 12" by Georg Ebers is a historical novel written during the late 19th century. The book chronicles a tumultuous period in Ancient Rome, exploring themes of tyranny, vengeance, and the quest for love amidst brutal events. The narrative primarily focuses on the reign of Emperor Caracalla and the aftermath of his violent reprisals in Alexandria, delving into the personal lives and struggles of characters intertwined with the emperor's fate. In this volume, the protagonist, Caracalla, grapples with the consequences of a massacre that he orchestrates in a fit of rage, claiming the lives of many Alexandrians. As the story unfolds, the reader follows Caracalla's descent into madness driven by guilt and fear, alongside the experiences of Melissa, a woman caught in the midst of political turmoil and personal tragedy. The narrative intertwines Melissa's journey towards faith and recovery, alongside her love for Alexander, and culminates in themes of redemption and hope amidst despair. The vivid depiction of the characters' emotional landscapes and their struggles against the backdrop of historical events creates a compelling and thought-provoking read that resonates with the complexities of human nature and morality. (This is an automatically generated summary.)s
Release date is 2004-04-01
This eBook was produced by David Widger
Keywords: Egypt -- History -- 30 B.C.-640 A.D. -- Fiction; German fiction -- Translations into English